Gestão municipal da educação, organização do sistema nacional e regime de colaboração: algumas questões - Tavares, Tais Moura (Educar em Revista, 2003)
Apesar da ambigüidade adquirida pelo termo público, partimos do pressuposto de que a educação é tarefa social sob responsabilidade do Estado. O federalismo brasileiro reparte o atendimento à educação nas diversas instâncias federativas. A ausência da efetivação do regime de cooperação e colaboração, apesar da existência de preceitos legais que a exigiriam, acentuou a fragmentação das políticas educacionais e a não constituição de um sistema nacional de educação. A municipalização do ensino fundamental tem sido instrumento de descentralização e tem reforçado a atomização das ações pedagógicas. Por outro lado, férteis experiências no âmbito da gestão municipal têm apresentado alternativas democráticas, particularmente no que se refere à gestão educacional. Municipal education management, organization of the national system and collaboration regime: some questions Abstract In spite of the acquired ambiguity of the term public, we broke of the presupposition that the education is social task under responsibility of the State. The Brazilian federalism distributes the service to the education in the several federal instances. The absence of execution of the cooperation regime and collaboration, in spite of the existence of legal precepts that were necessary, accentuated the fragmentation of the education politics and the non-constitution of a national system of education. The municipalização (kind of decentralization to the counties based on municipal management) of the fundamental teaching has been an instrument to reinforce the atomization of the pedagogic actions. On the other hand, fertile experiences in the extent of the municipal administration have presented democratic alternatives, particularly in which is referred to the education administration.